Canva-assisted Learning of Inquiry Sequences (LOIS)-based e-worksheet effectiveness - Kartini Herlina; Chandra Ertikanto; I Dewa Putu Nyeneng; Wayan Suane; B Anggit Wicaksono; Bizry Cahya Divia (Momentum: Physics Education Journal, 2023)
Education in Indonesia has undergone a transformation that was initially conventional but now necessitates the integration of technology. Materials for teaching that can aid students in learning are required. The purpose of this study is to explain how well the e-worksheet for learning dynamic fluid physics works. This research uses a modified ADDIE model for research and development. The viability of the e-worksheet is estimated using a learning accomplishment test. The subjects of this review were thirty understudies in class XI at SMA Negeri 5 Bandar Lampung. The side effect of the test shows that the feasibility of e-worksheets in the control class is low given the low rules of learning based on revelation learning. The effectiveness of e-worksheets in the experimental class is very high.